SISTEM INFORMASI WISATA KULINER BERBASIS WEB SEBAGAI MEDIA PROMOSI KULINER DI KOTA MALANG - Farida, Eni; Setyowibowo, Sigit (JURNAL TEKNOLOGI INFORMASI: Teori, Konsep, dan Implementasi, 2018)
Limited information about the place to eat in Malang city, such as food type, food price,eating location, dining hour become reference to provide complete information to tourists. To helptourists or local people looking for information on where to eat, needed a medium capable provideinformation on the address of the place to eat, the type of food served, the hours of operation, andthe price of food. The purpose of this research is the development of a web-based application ofculinary tourism information system in the city of Malang that can help the tourists or locals whowill find a place to eat recommendations in the city of Malang. Based on a series of stages ofresearch conducted it can be concluded that the culinary tourism information system in the city ofMalang can provide convenience for the tourists or residents in the search for information oneating places in Malang. Detailed and accurate information can help the tourists and localresidents in deciding where to eat they will choose Keywords: wisata, kuliner, wisatawan